SUMO: methods and protocols - Rodríguez, Manuel S. (Methods in molecular biology, 2016)
Concepts and Methodologies to Study Protein SUMOylation: An Overview -- The Regulation of Chromatin by Dynamic SUMO Modifications -- Reconstitution of the Recombinant RanBP1 SUMO E3 Ligase Complex -- Production and Purification of Recombinant SUMOylated Proteins Using Engineered Bacteria -- A Fluorescent In Vitro Assay to Investigate Paralog Specific SUMO Conjugation -- Identification and Characterization of SUMO-SIM Interactions -- Real-Time Surface Plasmon Resonance (SPR) for the Analysis of Interactions between SUMO-Traps and Mono or PolySUMO Moieties -- Using Biotinylated SUMO-Traps to Analyze SUMOylated Proteins -- In Vitro Characterization of Chain Depolymerization Activities of SUMO-Specific Proteases -- Detection of Protein SUMOylation In Situ by Proximity Ligation Assays -- In Situ SUMOylation and DeSUMOylation Assays: Fluorescent Methods to Visualize SUMOylation and DeSUMOylation in Permeabilized Cells -- Analysis of SUMOylated Proteins in Cells and In Vivo Using BioSUMO Strategy -- Label-Free Identification and Quantification of SUMO Target Proteins -- The Use of Multimeric Protein Scaffolds for Identifying Multi-SUMO Binding Proteins -- Isolation of In Vivo SUMOylated Chromatin-Bound Proteins -- Identification of Substrates of Protein-Group SUMOylation -- Tools to Study SUMO Conjugation in Caenorhabditis elegans -- Purification of SUMO Conjugates from Arabidopsis for Mass Spectrometry Analysis -- Detection of SUMOylation in Plasmodium falciparum -- Systematic Localization and Identification of SUMOylation Substrates in Knock-In Mice Expressing Affinity-Tagged SUMO1.